Bio-based synthesis of silver nanoparticles from orange waste: effects of distinct biomolecule coatings on size, morphology, and antimicrobial activity - Barros CHN (Dove Medical Press, 2018)
Caio Henrique Nasi de Barros, Guilherme Crispim Faria Cruz, Willian Mayrink, Ljubica Tasic Laboratory of Chemical Biology, Department of Organic Chemistry, Instituto de Química da Universidade Estadual de Campinas–Unicamp, Campinas, SP, Brazil Purpose: Despite the numerous reports on biological syntheses of silver nanoparticles (AgNPs), little is known about the composition of their capping agents, protein corona of plant extract-mediated synthesis, and their influence on the properties of AgNPs. Here, orange (Citrus sinensis) waste was utilized as a source of an extract for AgNP synthesis (the protein corona composition of which was elucidated), and also as a starting material for hesperidin and nanocellulose extraction, which were used for bio-based AgNP synthesis. A comparison of the results using the two methods of synthesis is presented. Methods: AgNPs were synthesized using orange (C. sinensis) peel extract (Or-AgNPs) in a biological route, and using hesperidin (Hsd-AgNPs) and nanocellulose (extracted from oranges) in a green chemical route. Characterization of nanoparticles was carried out using zeta potential and hydrodynamic size measurements, transmission electron microscopy, and X-ray diffraction. Elucidation of proteins from protein corona was performed via ultra performance liquid chromatography-tandem mass spectrometer experiments. Antimicrobial activity was assessed via minimum inhibitory concentration assays against Xanthomonas axonopodis pv. citri (Xac), the bacterium that causes citric canker in oranges. Results: Or-AgNPs were not completely uniform in morphology, having a size of 48.1±20.5 nm and a zeta potential of −19.0±0.4 mV. Stabilization was performed mainly by three proteins, which were identified by tandem mass spectrometry (MS/MS) experiments. Hsd-AgNPs were smaller (25.4±12.5 nm) and had uniform morphology. Nanocellulose provided a strong steric and electrostatic (−28.2±1.0 mV) stabilization to the nanoparticles. Both AgNPs presented roughly the same activity against Xac, with the minimum inhibitory concentration range between 22 and 24 μg mL−1. Conclusion: Despite the fact that different capping biomolecules on AgNPs had an influence on morphology, size, and stability of AgNPs, the antibacterial activity against Xac was not sensitive to this parameter. Moreover, three proteins from the protein corona of Or-AgNPs were identified. Keywords: silver nanoparticles, orange peel, Citrus sinensis, Xanthomonas, hesperidin